Oxidative profile of patients with osteoarthrosis undergoing total knee arthroplasty - Pierezan, Bruna (2017)
Introduction: Total knee arthroplasty may be the most appropriate method of treatment in several cases of osteoarthritis. This disease causes tissue damage, which is closely related to the production of free radicals, leading to oxidative stress and to lipid damage. Because of that, the body has several antioxidative defense systems involved in detoxification (antioxidants). Objective: Based on the previous information, the goal of this study was to establish the systemic and local oxidative profile of individuals with osteoarthritis submitted to total knee arthroplasty. Materials and methods: The sample consisted of four female patients (65.5 ± 0.7 years) with osteoarthritis of the knee. Blood and synovial fluid (SF) samples were collected from the patients 15 minutes before surgery. The concentrations of flavonoids, catalase, and TBARS were then quantified. Results: The results indicate a higher catalase activity in the SF than in the serum (S), (SF = 1 S = 14.3 ± 3.1 ± 0.8). The concentration of TBARS proved to be higher in the SF (SF = 0.29 ± 0.02 S = 0.09 ± 0.05), whereas the concentration of phenols was higher in the serum (SF = 3.2 S = 5.2 ± 0.2 ± 0.6). Conclusion: Osteoarthritis is a disease that increases the oxidative stress markers in the serum and in the SF.